HSP90/IKK‐rich small extracellular vesicles activate pro‐angiogenic melanoma‐associated fibroblasts via the NF‐κB/CXCL1 axis. Issue 4 (6th February 2022) - Tang, Hokeung; Zhou, Xiaocheng; Zhao, Xiaoping; Luo, Xinyue; Luo, Tingting; Chen, Yang; Liang, Weilian; Jiang, Erhui; Liu, Ke; Shao, Zhe; Shang, Zhengjun
Abstract: Hypoxia is a main feature of most solid tumors, but how melanoma cells under hypoxic conditions exploit tumor microenvironment (TME) to facilitate tumor progression remains poorly understood. In this study, we found that hypoxic melanoma‐derived small extracellular vesicles (sEVs) could improve the proangiogenic capability of cancer‐associated fibroblasts (CAFs). This improvement was due to the activation of the IKK/IκB/NF‐κB signaling pathway and upregulation of CXCL1 expression and secretion in CAFs. By proteomic analysis, we verified that hypoxia could promote enrichment of chaperone HSP90 and client protein phosphorylated IKKα/β (p‐IKKα/β) in melanoma‐derived sEVs. Delivery of the HSP90/p‐IKKα/β complex by sEVs could activate the IKK/IκB/NF‐κB/CXCL1 axis in CAFs and promote angiogenesis in vitro and in vivo. Taken together, these findings deepen the understanding of hypoxic response in melanoma progression and provide potential targets for melanoma treatment. Abstract : Hypoxia could promote enrichment of the HSP90/p‐IKKα/β complex in melanoma‐derived small extracellular vesicles (sEVs). Transfer of HSP90/p‐IKKα/β to cancer‐associated fibroblasts (CAFs) by sEVs could activate the IKK/IκB/NF‐κB signaling pathway and promote CXCL1 expression and secretion in CAFs, which led to melanoma angiogenesis and progression.